Assessing University Website Performance: A Comparative Analysis Using GTmetrix - Davin Nayaka Pandya; Doddy Suryadharma; Lili Ayu Wulandhari; Islam Nur Alam (International Journal of Computer Science and Humanitarian AI, 2024)
As the reliance on websites to disseminate information increases, universities are no exception, using websites as an important platform for their information systems. However, ensuring optimal website performance is imperative, as slow or unresponsive websites can lead to decreased user satisfaction and affect the university's reputation. This study aims to analyze and compare the performance of university information system websites from Indonesia’s top five universities against the world’s leading institutions in Computer Science and Information Systems based on QS World University Rankings by Subject 2023. Utilizing GTmetrix, a comprehensive performance assessment tool, key performance metrics such as First Contentful Paint (FCP), Speed Index (SI), Largest Contentful Paint (LCP), Time to Interactive (TTI), Total Blocking Time (TBT), and Cumulative Layout Shift (CLS) were evaluated. The findings reveal a significant performance gap between the top universities globally and in Indonesia. While global universities demonstrate good performance across various metrics, Indonesian universities exhibit areas in need of improvement, particularly in metrics like FCP, SI, LCP, TTI, and CLS. Nevertheless, Indonesian universities excel in blocking time, suggesting strategic strengths that can be leveraged for overall performance enhancement. This study underscores the importance of regular attention to website performance to enhance user experience and maintain the university's reputation within the academic community.